Education for Sustainable Development and STEM Integration in Environmental Project-Based Learning at Madrasah Ibtidaiyah - Ahsani, Eva Luthfi Fakhru; Naili Luma’ati Noor; Mochammad Jaza Al Aufa; Yuliana Noor Annisa (UIN Sunan Kalijaga Yogyakarta, 2026)
The integration of Education for Sustainable Development (ESD) and STEM Education is important in primary education; however, its implementation in Madrasah Ibtidaiyah remains underexplored, particularly in utilizing the school environment as a contextual learning resource. This study aims to analyze teachers’ understanding of ESD and STEM integration, examine the role of the school environment in supporting learning, and identify how ESD and STEM are integrated into environmental project-based learning. This research employed a descriptive qualitative approach involving fifth-grade students, teachers, and the principal of a Madrasah Ibtidaiyah in Blora Regency. Data were collected through observation, interviews, and documentation and analyzed through data reduction, data display, and conclusion drawing. The findings show that teachers understood ESD through environmental care practices and applied STEM through contextual problem-solving activities, although challenges remained in integrating all STEM components systematically. The school environment functioned as a learning laboratory through waste management, plant observation, and simple water filtration projects using local materials. This study contributes to the development of contextual ESD-STEM learning models in Madrasah Ibtidaiyah through environmental project-based learning that integrates sustainability values with STEM competencies.